2010
DOI: 10.1161/hypertensionaha.110.157685
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Antagonist Etanercept Decreases Blood Pressure and Protects the Kidney in a Mouse Model of Systemic Lupus Erythematosus

Abstract: Abstract-Chronic inflammation has been implicated in the pathology of hypertension; however, the role for specific cytokines remains unclear. We tested whether tumor necrosis factor-␣ blockade with etanercept (Etan) reduces mean arterial pressure in a female mouse model of systemic lupus erythematosus (SLE). SLE is a chronic inflammatory disorder with prevalent hypertension. and lowered in Etan-treated SLE mice (6645Ϯ490). Renal cortex nuclear factor B (phosphorylated and nonphosphorylated) was increased in SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
138
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(152 citation statements)
references
References 48 publications
14
138
0
Order By: Relevance
“…Consistent with our present findings, Venegas et al (48) reported that ETN suppresses a downstream signaling of target of TNF-␣, such as NF-B in the renal cortex, although ETN did not affect the expression of membrane TNF-␣ in a mouse model of systemic lupus erythematosus. This lack of drug effect might be attributable to the following characteristics of ETN.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our present findings, Venegas et al (48) reported that ETN suppresses a downstream signaling of target of TNF-␣, such as NF-B in the renal cortex, although ETN did not affect the expression of membrane TNF-␣ in a mouse model of systemic lupus erythematosus. This lack of drug effect might be attributable to the following characteristics of ETN.…”
Section: Discussionsupporting
confidence: 92%
“…This lack of drug effect might be attributable to the following characteristics of ETN. First, ETN predominantly binds to circulating (soluble) TNF-␣ and does not affect the expression of membrane TNF-␣ in the kidney (48). Second, the binding of ETN (a diametric molecule) to membrane TNF-␣ is not as strong as that of infliximab (a trimeric molecule) due to the differences in structure, raising the possibility that ETN causes a decrease in TNF-␣ activity but that the effect is not strong enough to decrease membrane TNF-␣ expression in the kidney (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have observed that the amount of TNF-a is reduced by IFN-g treatment in the skin of cpdm mice. To confirm the involvement of TNF-a in cpdm, we treated cpdm mice with etanercept, which blocks the effect of TNF-a (37,38). Etanercept treatment ameliorated cpdm and inhibited keratinocyte apoptosis and infiltration of inflammatory cells such as granulocytes, macrophages, and mast cells (Supplemental Fig.…”
Section: Reduction Of Macrophage Neutrophil and Mast Cell Infiltratmentioning
confidence: 99%
“…These data seem to indicate that TNF-␣ mediates ANG II-dependent increases in blood pressure. Similarly, in a mouse model of lupus erythematosus etanercept infusion for 4 wk reduced blood pressure, albuminuria, glomerulosclerosis, and NF-B activity, suggesting that TNF-␣ causes inflammation and mediates the increase in blood pressure (152).…”
mentioning
confidence: 94%